2020
DOI: 10.3389/fimmu.2019.03033
|View full text |Cite
|
Sign up to set email alerts
|

Single Eye mRNA-Seq Reveals Normalisation of the Retinal Microglial Transcriptome Following Acute Inflammation

Abstract: Background: Whether retinal microglia can maintain or restore immune homeostasis during and after inflammation is unclear. We performed single-eye mRNA-sequencing on microglia at different timepoints following a single inflammatory stimulus to characterise their transcriptome during and after resolution of endotoxin-induced uveitis (EIU). Experimental Approach: Cx3cr1 CreER :R26-tdTomato (C57BL/6) male heterozygotes were administered tamoxifen via different regimes at 4-5 weeks of age. Four weeks post-tamoxife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Moreover, SMART-Seq v4 is more efficient in template switching, which shortens the time of cDNA synthesis and cDNA library construction, and has a higher sensitivity for low input and higher reproducibility [ 28 ]. SMART-Seq v2 and v4 are widely utilized in cancer research, such as research on hepatocellular carcinoma (HCC) [ 29 31 ]. In addition, SMART-Seq does not require additional equipment, which means that it largely depends on experienced researchers.…”
Section: Emerging Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…Moreover, SMART-Seq v4 is more efficient in template switching, which shortens the time of cDNA synthesis and cDNA library construction, and has a higher sensitivity for low input and higher reproducibility [ 28 ]. SMART-Seq v2 and v4 are widely utilized in cancer research, such as research on hepatocellular carcinoma (HCC) [ 29 31 ]. In addition, SMART-Seq does not require additional equipment, which means that it largely depends on experienced researchers.…”
Section: Emerging Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…Vol. :(0123456789) Scientific Reports | (2020) 10:16967 | https://doi.org/10.1038/s41598-020-73749-y www.nature.com/scientificreports/ Interestingly, microglia are capable of defaulting to the baseline, homeostatic transcriptome weeks after acute inflammation in endotoxin uveitis 47 . On the other hand, microglia in slowly progressive forms of RP may remain pro-inflammatory even after significant photoreceptor loss, which has been demonstrated in the P23H RHO rat 48 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that microglia in the I307N Rho mouse reduce in number, move towards homeostatic positioning among the retinal layers, and exhibit a more ramified phenotype in the weeks following light exposure. Interestingly, microglia are capable of defaulting to the baseline, homeostatic transcriptome weeks after acute inflammation in endotoxin uveitis 47 . On the other hand, microglia in slowly progressive forms of RP may remain pro-inflammatory even after significant photoreceptor loss, which has been demonstrated in the P23H RHO rat 48 .…”
Section: Discussionmentioning
confidence: 99%
“…One essential tool for advancing understanding of these different tissue states is a rigorous method of clinical assessment that separates healthy tissue from the vulnerable and that also distinguishes between different states of the vulnerable tissue. Such a scheme could then complement studies describing gene expression in different forms of ocular inflammation (13,40). Recent advances in the range and quality of techniques that can be applied to quantify ocular inflammatory disease make such objective and transferrable assessments increasingly feasible.…”
Section: Ocular Tissue and Inflammationmentioning
confidence: 99%
“…experimental autoimmune uveitis; EAU), inspired in the mouse by early work identifying susceptible strains (3,4) and used widely to probe important aspects of immune function including tolerance (5,6), regulation (7,8), microbiome (9), lymphocyte dynamics (10) and macrophage/monocyte function (11). But other models of ocular inflammation are also important, including endotoxin induced uveitis (EIU) (12)(13)(14) and primed mycobacterial uveitis (PMU) (15). Ocular infectious disease can also be studied and has proven to be an informative model of inflammation (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%